Neuromuscular fatigue depends on relative blood-flow restriction levels - Fatela, P.; Reis, J.; Mendonça, G.; Avela, J.; Mil-Homens, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The acute neuromuscular response to blood flow restriction exercise (BFRE) is yet to be understood, particularly with different relative levels of BFR. This study aimed to resolve methodological limitations reported in literature (Loenneke, 2015), and to extent the findings of past research on the neuromuscular adaptations to BFRE performed at different levels of pressure (Loenneke, 2015; Yasuda, 2008). We examined the acute effects of low-intensity knee extensions (20% 1RM) with BFR, on neuromuscular fatigue and torque of the rectus femoris (RF) and vastus medialis (VM) muscles. Methods: Fourteen young men (24.8±5.4 yrs; height: 175.2±4.4 cm; body mass: 71.1±6.9 kg) were tested on 3 different conditions of unilateral knee extension exercise (20% 1RM: 4 sets of 30+15+15+15 reps) with BFR. Conditions were determined by various BFR levels normalized to the pressure value of absolute vascular occlusion, determined at rest (40, 60 and 80%BFR). Torque was collected from a Biodex System 3 (Shirley, NY), during pre and post-exercise MVCs. Neuromuscular fatigue was determined through EMG signal - median frequency (MF); using Trigno™ wireless system (Delsys, USA). MF was calculated through 3 sustained isometric contractions (20% MVC), at 4 time-points: pre 1 - baseline; pre 2 - 1 min after cuff inflation; post 1 - immediately after exercise; post 2 - 1 min after cuff release. Paired t tests were used to explore differences in torque and MF parameters, for each condition (40, 60 and 80%BFR). A two-way repeated measures ANOVA [condition (40 vs. 60 vs. 80%BFR) x time (pre1 vs. pre2 vs. post1 vs. post2)] was conducted to determine the effects pre to post-exercise on MF. Results: Torque only decreased (-5.2%) in the 80%BFR condition (p<0.01). One minute after cuff inflation (pre1 to pre2), MF was only significantly different in the 80% BFR condition for the RF muscle (-7.8%, p<0.01). After exercise with various levels of BFR (pre2 to post1), MF decreased significantly in the RF muscle (40%BFR: -8.4%, 60%BFR: -15.2%, 80%BFR: -21.2%, p<0.01) and in the VM muscle (60%BFR: -3.2%, 80%BFR: -7.5%, p<0.01). After cuff release (post1 to post2), MF increased significantly in both muscles for all conditions, although MF of the RF was still significantly different between pre1 and post 2 (-11.8%, p<0.01), after the 80%BFR condition. Discussion: This study demonstrated that the magnitude and duration of neuromuscular fatigue is dependent on the relative level of vascular restriction. Accordingly, within resistance training context, BFR should not be prescribed using standardized values of occlusion pressure, as the relationship between relative and absolute values of BFR pressure can be very different.